2013
DOI: 10.2337/dc13-0266
|View full text |Cite
|
Sign up to set email alerts
|

Type A Behavior and Risk of All-Cause Mortality, CAD, and CAD-Related Mortality in a Type 1 Diabetic Population: 22 Years of Follow-up in the Pittsburgh Epidemiology of Diabetes Complications Study

Abstract: OBJECTIVETo determine whether type A behavior predicts all-cause mortality and incident coronary artery disease (CAD) in a type 1 diabetic population.RESEARCH DESIGN AND METHODSFollow-up data (22 years) from the Pittsburgh Epidemiology of Diabetes Complications (EDC) study of childhood-onset type 1 diabetes were analyzed for the 506 participants who completed the Bortner Rating Scale (measuring type A behavior) and Beck Depression Inventory (BDI) at baseline (1986–1988). CAD comprised myocardial infarction as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…Fickley et al [4] revealed that, in type 1 diabetes, cardiac and all-cause mortality rates were lower in people with Type A personality. The present study is therefore consistent with the Fickley report, and suggests that Type A might be associated with reduced mortality through lower levels of systemic inflammation in patients with diabetes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Fickley et al [4] revealed that, in type 1 diabetes, cardiac and all-cause mortality rates were lower in people with Type A personality. The present study is therefore consistent with the Fickley report, and suggests that Type A might be associated with reduced mortality through lower levels of systemic inflammation in patients with diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…In the context of chronic diseases, Type A personality was even associated with increased survival in people with coronary heart disease [1]. Also, Type A was recently associated with lower cardiovascular and all-cause mortality in type 1 diabetes [4]. It is worth mentioning that the association between Type A personality and lower mortality in patients with diabetes [4] was found with the Bortner Type A rating scale, which captures time urgency, job involvement and competitiveness dimensions, but not hostility.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Many studies have established the relationship of personality of an individual as risk factor of heart diseases, cancer, injuries and mental disorders. 2,3 People with Type A personality traits are aggressive, ambitious, highly competitive, preoccupied with status, workaholics, hostile, and lack patience and traits of Type B personality are relaxed, less stressed, flexible, emotional and expressive, and have a laid-back attitude. The personality of the Type C or ''anger in'' personality is described as a repressive and vigilant personality pattern.…”
Section: Introductionmentioning
confidence: 99%